Variations in Bioactive Content in Different Tomato Trusses due to Elicitor Effects - Luciano Ávila-Juárez; Herminio Miranda-Rodríguez (Journal of Chemistry)
The tomato fruit is rich in bioactive compounds with antioxidant activity, the levels of which can vary over time in response to biotic and abiotic factors, including the application of elicitors. We investigated the effects of foliar spray of methyl jasmonate (MeJ), salicylic acid (SA), nitric oxide (NO), and hydrogen peroxide (H2O2) on tomato plants every 15 days until the end of cultivation. We measured the levels of bioactive compounds, antioxidant activity, and physiological parameters in three distinct trusses. With the exception of plant length, the elicitors had no effects on physiological parameters, whereas they did have an effect on lycopene content, bioactive compound levels, and antioxidant activity in the three sampled trusses. A strong correlation between bioactive compounds and antioxidant activity was found for the elicitors, particularly MeJ. Our results indicate that certain bioactive compounds and their antioxidant activities vary not only between trusses but also based on the specific elicitor used.